Minutes of the Twenty-eighth Regular Meeting of The Rocky Mountain Coal Mining Institute held at Salt Lake City, Utah March 11, 12 and 13, 1929 (Rocky Mountain Coal Mining Institute, 1929)
The twenty-eighth regular meeting of the Rocky Mountain Coal Mining Institute, which was held jointly with the Utah Section of the American Institute of Mining and Metallurgical Engineers, was called to order at eleven o'clock A. M., Monday, March 11, 1929, President Otto Herres presiding. Introductory remarks were made by John M. Boutwell, Chairman of the Utah Section of the American Institute of Mining and Metallurgical Engineers, who outlined the intent and purpose of the joint meeting, and its co-operative program. He spoke of the in- creased recognition being given to men in the engineering profession by the public, which has recently been manifested by the election of President Hoover, an engineer of outstanding ability, and the re-election of Governor Dern to the Governorship of the State of Utah. He then introduced Governor Dern, a fellow member, to make the address of welcome. Governor Dern assured the meeting a hearty welcome. He spoke of Utah as one of the important mining states of the Union, particularly in metal mining; the magnitude of Utah as a coal mining state being limited only by its market; of the enormous coal resources of Utah, and the problems of the coal mining industry.